Prevalence of Hypothyroidism in Pregnancy: A Single-Center Study from a Tertiary Referral Center in Kathmandu, Nepal - Mall, D; Karki, BB; Bajracharya, MR; Shrestha, PS; Maharjan, R (Journal of Diabetes and Endocrinology Association of Nepal, 2025)
Background: Hypothyroidism in pregnancy is associated with adverse maternal and fetal outcomes. Despite increasing awareness, data from Nepal remain limited. Objective: To determine the prevalence of hypothyroidism among pregnant women referred to a tertiary center in Kathmandu and to evaluate the demographic and clinical profiles of these patients.Methods: A retrospective observational study was conducted at Endocrine out patients, Bir Hospital, National Academy of Medical Sciences (NAMS), Kathmandu, from January 2021 to January 2023. A total of 189 pregnant women referred from various maternity centers for elevated TSH were included. Clinical characteristics, trimester-specific thyroid levels, and treatment status were analyzed.Results: Among 189 pregnant women, 62 (32.8%) were primigravida and 127 (67.2%) were multigravida. Of these, 106 (56.1%) were already on thyroxine supplementation before conception. Thyroid dysfunction was managed per ATA and Indian Thyroid Association guidelines. Most referrals occurred in the first and second trimesters. The youngest participant was 17 years and the oldest 43 years.Conclusion: A substantial proportion of pregnant women were diagnosed with or had pre-existing hypothyroidism. Routine screening and pre-conceptional thyroid assessment are crucial for ensuring optimal pregnancy outcomes. Longitudinal studies are warranted to evaluate maternal-fetal outcomes in hypothyroid pregnancies in Nepal